Perancangan Sistem Microsoft Office Access pada Toko Batam Sumber Indah - Dea Tiara Monalisa Butar-Butar; Stefy (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
Financial reports are a source of information that stakeholders use to make decisions regarding controlling company operational costs, understanding company profits and losses, understanding debts and liabilities, and calculating taxes. As financial reports also play an important role in Micro Small and Medium Enterprises sector, there are still many Micro Small and Medium Enterprises sector that have not prepared financial reports or have prepared them in the middle of difficulties and complications. This community service activity is carried out using survey and interview methods. After finding the obstacles faced by Batam Sumber Indah Store, the solution was to design an accounting system information in the form of Microsoft Office Access. The results of this activity are expected to increase the efficiency and effectiveness of the Batam Sumber Indah Store in producing reliable financial reports.